THE ROLE OF WORK DISCIPLINE AND CAREER DEVELOPMENT ON LOYALTY OF EMPLOYEES IN GOLF MANAGEMENT COMPANY - Ratnawita Ratnawita; Santi Nururly; Mohammad Rofik; Ansri Jayanti; Wina Aset (Jurnal Scientia, 2023)
The purpose of this study is to ascertain whether career advancement and work ethic have an impact on employee loyalty either separately or together. The primary and secondary data used in this study were gathered from the field and libraries. 59 employees made up the sample for this investigation. by applying a basic random sampling technique. Quantitative research is used in this field. Multiple linear regression analysis with SPSS 26 is the analytical approach employed. The findings of this study show that work discipline and career growth have a considerable impact on employee loyalty, either separately or in combination.